Model of structure-semantic representation and software profiles transformation: operation of combination - Gordieiev, O.O.; Lapshin, A. L. (Systems and Technologies, 2020)
The article considers the problem of describing the formalization of software profiling. The primary task of software profiling formalizing is the task of presenting and describing of software profiles. In the article, it is solved by representing the software profile in the form of semantic taxonomic structures (hierarchies, facets and mixed structures). Thus, each software profile consists of a structure (many taxa and classification features) and semantic content. For example, in the article, the requirements profile is presented in the form of a semantic taxonomic structure – a hierarchy in the semantic filling of taxa and classification features at the level of words from the requirements. Those. an indivisible semantic unit is a word in a sentence. As an example, in the article, the semantic indivisible unit is the word in the software requirements sentence. It is worth noting that the set of elements of the sets of taxa and classification features are presented in the form of cartage, since for each word its position in the sentence is important. To perform the process of profiling and forming of a software profile, the operation of combining semantic taxonomic structures is considered and formally described. For its implementation, separate types of union operations are introduced: union in width, union in depth and mixed union. It also describes the conditions under which these types of merge operations can be used for profiling. When combining semantic taxonomic structures, the degree of correspondence of such structures with each other is formulated and formally described: strong, permissible, and weak. The degree of correspondence when combining semantic taxonomic structures, which will be necessary when combining semantic taxonomic structures, is determined by the expert. To perform the operation of combining semantic taxonomic structures, an algorithm for performing such an operation is described in detail. The article graphically presents and formally describes the options for combining hierarchical and facet structures – a total of 12 variants for each type of semantic taxonomic structures.